Long- and Short-term Exposure to Air Pollution and Inflammatory/Hemostatic Markers in Midlife Women. Issue 2 (March 2016) - Green, Rochelle; Broadwin, Rachel; Malig, Brian; Basu, Rupa; Gold, Ellen B.; Qi, Lihong; Sternfeld, Barbara; Bromberger, Joyce T.; Greendale, Gail A.; Kravitz, Howard M.; Tomey, Kristin; Matthews, Karen; et al.
Abstract : Background: Studies have reported associations between long-term air pollution exposures and cardiovascular mortality. The biological mechanisms connecting them remain uncertain. Methods: We examined associations of fine particles (PM2.5 ) and ozone with serum markers of cardiovascular disease risk in a cohort of midlife women. We obtained information from women enrolled at six sites in the multi-ethnic, longitudinal Study of Women's Health Across the Nation, including repeated measurements of high-sensitivity C-reactive protein, fibrinogen, tissue-type plasminogen activator antigen, plasminogen activator inhibitor type 1, and factor VIIc (factor VII coagulant activity). We obtained residence-proximate PM2.5 and ozone monitoring data for a maximum five annual visits, calculating prior year, 6-month, 1-month, and 1-day exposures and their relations to serum markers using longitudinal mixed models. Results: For the 2, 086 women studied from 1999 to 2004, PM2.5 exposures were associated with all blood markers except factor VIIc after adjusting for age, race/ethnicity, education, site, body mass index, smoking, and recent alcohol use. Adjusted associations were strongest for prior year exposures for high-sensitivity C-reactive protein (21% increase per 10 μg/m 3 PM2.5, 95% confidence interval [CI]: 6.6, 37), tissue-type plasminogen activator antigen (8.6%, 95% CI: 1.8, 16), and plasminogen activator inhibitor (35%, 95% CI: 19, 53). An association was also observed between year prior ozone exposure and factor VIIc (5.7% increase per 10 ppb ozone, 95% CI: 2.9, 8.5). Conclusions: Our findings suggest that prior year exposures to PM2.5 and ozone are associated with adverse effects on inflammatory and hemostatic pathways for cardiovascular outcomes in midlife women. Abstract : Supplemental Digital Content is available in the text.